The Influence of Culture and Time on Any Research Regarding Ethics - Andrei Tabarcea (CES Working Papers, 2013)
The current study presents the most important theoretical frameworks in the field of ethical behavior involving employees and shows how the results of previous research are influenced by culture and time. At the same time, the risks that follow the universalization of the results are presented and a series of recommendations are made for researchers in the field, in order to obtain valuable results.
Keywords: A13; 330; ethical behavior; culture; time; universalization Romania